Does size of tendon gap affect patient-reported outcome following Achilles tendon rupture treated with functional rehabilitation?. (1st November 2020) - Yassin, Mohamed; Myatt, Richard; Thomas, William; Gupta, Vatsal; Hoque, Tagrit; Mahadevan, Devendra
Abstract : Aims: Functional rehabilitation has become an increasingly popular treatment for Achilles tendon rupture (ATR), providing comparably low re-rupture rates to surgery, while avoiding risks of surgical complications. Limited evidence exists on whether gap size should affect patient selection for this treatment option. The aim of this study was to assess if size of gap between ruptured tendon ends affects patient-reported outcome following ATR treated with functional rehabilitation. Methods: Analysis of prospectively collected data on all 131 patients diagnosed with ATR at Royal Berkshire Hospital, UK, from August 2016 to January 2019 and managed non-operatively was performed. Diagnosis was confirmed on all patients by dynamic ultrasound scanning and gap size measured with ankle in full plantarflexion. Functional rehabilitation using an established protocol was the preferred treatment. All non-operatively treated patients with completed Achilles Tendon Rupture Scores (ATRS) at a minimum of 12 months following injury were included. Results: In all, 82 patients with completed ATRS were included in the analysis. Their mean age was 51 years (standard deviation (SD) 14). The mean ATRS was 76 (SD 19) at a mean follow-up of 20 months (SD 11) following injury. Gap inversely affected ATRS with a Pearson's correlation of -0.30 (p = 0.008). Mean ATRS was lower with gaps > 5 mm compared with ≤ 5 mm (73 (SD 21) vs 82 (SD 16); p = 0.031). Mean ATRS was lowest (70 (SD 23)) with gaps > 10 mm, with significant differences in perceived strength and pain. The overall re-rupture rate was two out of 131 (1.5%). Conclusion: Increasing gap size predicts lower patient-reported outcome, as measured by ATRS. Tendon gap > 5 mm may be a useful predictor in physically demanding individuals, and tendon gap > 10 mm for those with low physical demand. Further studies that control for gap size when comparing non-operative and operative treatment are required to assess if these patients may benefit from surgery, particularly when balanced against the surgical risks. Cite this article: Bone Joint J 2020;102-B(11):1535–1541.